2011
DOI: 10.1039/c1cc10993f
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of porous silicon microparticles for the long-term delivery of redox-active therapeutics

Abstract: Thermal oxidation of porous Si microparticles provides an inert carrier for the long-term release of the anthracycline drug daunorubicin. Without prior oxidation, porous Si undergoes an undesirable side reaction with this redox active drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 17 publications
(23 reference statements)
0
48
0
1
Order By: Relevance
“…To determine the amount of DNR loaded, pSi microparticles were completely dissolved in a solution of 1 M sodium hydroxide (Sigma-Aldrich) and the solution was neutralized with 1 M hydrochloric acid (Sigma-Aldrich) to recover the fluorescence spectrum of the free drug as previously described. 26 The calculated quantity of DNR loaded was 22 mg per 1 mg of pSi particles. 13 …”
Section: Drug Loadingmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the amount of DNR loaded, pSi microparticles were completely dissolved in a solution of 1 M sodium hydroxide (Sigma-Aldrich) and the solution was neutralized with 1 M hydrochloric acid (Sigma-Aldrich) to recover the fluorescence spectrum of the free drug as previously described. 26 The calculated quantity of DNR loaded was 22 mg per 1 mg of pSi particles. 13 …”
Section: Drug Loadingmentioning
confidence: 99%
“…In our previous in vitro study, reduced DNR was observed, and the degradation products from this hydrosilylated pSi delivery system showed increased potency toward RPE cells. 26 In the present in vivo study, the same delivery system and the payload did not induce any signs of ocular toxicity or other deleterious effects during 6 months of the study. It is known that pSi degrades into silicic acid, which is presumably cleared with physiological vitreous fluid turnover.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…This procedure results in a functional pSi surface grafted with C-10 alkyls containing terminal carboxyl groups (-COOH). A significant quantity of the surface hydrides (Si-H) remaining after the hydrosilylation reaction were eliminated by air oxidation at 150 °C for 48 hours in a ceramic boat inside a muffle furnace (Thermo Fisher Scientific, Pittsburg, PA), as previously described 23 . The functionalized samples were kept under vacuum in a desiccator.…”
Section: Hydrosilylation Of Undecylenic Acidmentioning
confidence: 99%